Cellular context determines primary characteristics of human TRPC5 as a cold-activated channel - Ptakova, Alexandra; Mitro, Michal; Zimova, Lucie; Vlachova, Viktorie (Journal of cellular physiology, 2022)
The human transient receptor potential canonical 5 (TRPC5) is a calcium-permeable, nonselective cation channel expressed in the central and peripheral nervous system and also in other tissues such as the kidney, synovium, and odontoblasts. TRPC5 has been recently confirmed to play a key role in spontaneous, inflammatory mechanical, and cold pain. Although TRPC5 activation is known to be cold sensitive, it is unclear whether this property is intrinsic to the channel protein and whether or to what extent it may be determined by the cellular environment. In this study, we explored the cold sensitivity of human TRPC5 at the single-channel level using transiently transfected HEK293T cells. Upon decreasing the temperature, the channel demonstrated prolonged mean open dwell times and a robust increase in the open probability (Po ), whereas the amplitude of unitary currents decreased ~1.5-fold per 10°C of temperature difference. In the absence of any agonists, the temperature dependence of Po was sigmoidal, with a steep slope within the temperature range of 16°C-11°C, and exhibited saturation below 8-5°C. Thermodynamic analysis revealed significant changes in enthalpy and entropy, suggesting that substantial conformational changes accompany cold-induced gating. The mutant channel T970A, in which the regulation downstream of G-protein coupled receptor signaling was abrogated, exhibited higher basal activity at room temperature and a less steep temperature response profile, with an apparent threshold below 22°C. An even more pronounced decrease in the activation threshold was observed in a mutant that disrupted the electrostatic interaction of TRPC5 with the endoplasmic reticulum calcium sensor stromal interaction molecule 1. Thus, TRPC5 exhibits features of an intrinsically cold-gated channel; its sensitivity to cold tightly depends on the phosphorylation status of the protein and intracellular calcium homeostasis.
Keywords: buněčná membrána; TRPC cation channels; Calcium; vápník; vápníkové kanály; kationtové kanály TRPC; TRPC Cation Channels; HEK293T; Calcium Channels; single channels; HEK293 buňky; Humans; cold temperature; thermosensitive TRP; HEK293 Cells; stromal interaction molecule 1; lidé; Cell Membrane